2022
DOI: 10.1002/adma.202202574
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Long‐Alkyl‐Group Spacers in Glycolated Copolymers for High‐Performance Organic Electrochemical Transistors

Abstract: Semiconducting polymers with oligoethylene glycol (OEG) sidechains have attracted strong research interest for organic electrochemical transistor (OECT) applications. However, key molecular design rules for high-performance OECTs via efficient mixed electronic/ionic charge transport are still unclear. In this work, new glycolated copolymers (gDPP-TTT and gDPP-TTVTT) with diketopyrrolopyrrole (DPP) acceptor and thiophene (T) and vinylene (V) thiophene-based donor units are synthesized and characterized for accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…[ 52 ] Confirming that the two gTNR derivatives can be reduced efficiently in aqueous solution, we also notice a more intense polaron absorption band for lgTNR than for bgTNR at identical electrochemical potentials (Figure 3f) which could indicate a better ability for the linear derivative to accommodate stored charges in the semiconductor film compared to the branched counterpart under these conditions. [ 53 ] We also investigated the polaron stability of the two semiconductors by monitoring the intensity changes of UV‐vis–NIR absorption spectra during continuous electrochemical cycling. Both lgTNR and bgTNR exhibit moderate polaron stability with a retention of 80% and 70% optical density after ten cycles (Figure S8, Supporting Information), which corroborate the morphological changes observed after cycling, and the OECT operational stability discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…[ 52 ] Confirming that the two gTNR derivatives can be reduced efficiently in aqueous solution, we also notice a more intense polaron absorption band for lgTNR than for bgTNR at identical electrochemical potentials (Figure 3f) which could indicate a better ability for the linear derivative to accommodate stored charges in the semiconductor film compared to the branched counterpart under these conditions. [ 53 ] We also investigated the polaron stability of the two semiconductors by monitoring the intensity changes of UV‐vis–NIR absorption spectra during continuous electrochemical cycling. Both lgTNR and bgTNR exhibit moderate polaron stability with a retention of 80% and 70% optical density after ten cycles (Figure S8, Supporting Information), which corroborate the morphological changes observed after cycling, and the OECT operational stability discussed below.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed procedures for Y- n C-4O synthesis, material characterizations, device fabrication, and measurements are described in the Supporting Information. Intermediate compounds for the guest SMAs were synthesized according to previous literature. , The poly­(3,4-ethylenedioxythiophene):poly­(styrenesulfonate) (PEDOT:PSS, Clevios P VP AI 4083) solution, used to prepare the hole-transporting layer, was purchased from Heraeus (Germany). PM6 and Y6, used as the polymer donor and host SMA, respectively, were purchased from Derthon OPV.…”
Section: Methodsmentioning
confidence: 99%
“…Another study from the same team demonstrated the preferential interactions of ions with the donor (anions) or acceptor (cations) units of glycolated diketopyrrolopyrrole (DPP)-based copolymers and how the side chain nature could influence such interactions for maximized OECT performance. 161 Furthermore, MD simulations were successfully used to study phase transitions in OMIECs amorphous phase during electrochemical doping and ion injection, [162][163][164] despite relying on AMBER force a non-validated force field model for the systems investigated and generally used to model nonconjugated system. 165 To accurately model OMIECs, a possible alternative is to reparametrize backbone dihedral angles to capture more accurately the torsional behavior of the conjugated units.…”
Section: Theoretical Approachesmentioning
confidence: 99%